Hereditary hemochromatosis gene mutations in patients with myocardial infarction - Škrlec, Ivana (Array, 2019)
Hereditary hemochromatosis (HH) is a disorder of iron accumulation in tissues, which is related to coronary heart diseases. Free radicals and reactive oxygen species, created because of iron deposition, promote oxidation of LDL cholesterol and could lead to the development of atherosclerosis. Studies have shown that HFE gene mutation carriers might be at higher risk of developing cardiovascular diseases compared with non-carriers. This study aimed to determine the frequency of HFE gene mutations in patients with myocardial infarction compared to a healthy group in eastern Slavonia. A retrospective case-control study was carried out on a population of 400 participants. In the first group there were 200 patients (114 males and 86 females) with myocardial infarction. The second group consisted of 200 controls (103 males and 97 females) without a history of cardiovascular diseases. All patients were genotyped for the three most common mutations of the HH in the HFE gene: C282Y, H63D, and S65C, by real-time PCR. The difference in the frequency of carriers of these mutations between the patients and the controls was not significant (C282Y: 4.5 vs. 8.1%; H63D: 19 vs. 24.5%; S65C: 3.5 versus 4%), and neither was the frequency and distribution of possible HFE gene genotypes and compound heterozygotes. There were no statistically significant associations of cardiovascular risk factors and HFE gene mutations in patients with myocardial infarction. In this study, no association was found between the HFE gene mutation for HH and myocardial infarction in the population of eastern Slavonia.